50 fantastic ideas for storytelling - Horvath, Judit (London : Featherstone, 2007)
Amongst many popular activities, listening to and telling stories is fundamental to every early years setting. Apart from being fun and exciting, storytelling has many functions in children$1 (Bs development, helping them to make sense of the world and organize events and experience. Children often retell their adventures as stories, from the simple event of having dinner to major happenings such as falling down the stairs! The story organizes events from the past and as they happen, and both the story and its telling convey important information about relationships, thoughts and feelings and the children$1 (Bs personal life in general. This book contains simple but creative ideas to help practitioners prompt and aid storytelling for and with the children in their setting.s
Keywords: Storytelling in education; Early childhood education; EDUCATION -- Elementary